Assessment of the effect of Pranayama on pulmonary function: Comparison among vegetarian and non- vegetarian healthy young adults - Yadav, Renu; Kumar Yadav, Subodh; Kumari Shah, Ranjana (Journal of Chitwan Medical College, 2026)
Introduction: Yoga, an ancient physical exercise, promotes holistic well-being through practices like Pranayama. Diet may also affect respiratory health. This study assessed pulmonary function test (PFT) parameters among vegetarians and non-vegetarians before and after Pranayama.Method: This quasi-experimental study was conducted at Birat Medical College, Nepal, from 15 Oct to 31 Dec after ethical approval. Healthy medical students were enrolled in vegetarian (Group A) and non-vegetarian (Group B) groups for one month of pranayama practice. Current smokers, those with recent respiratory infections, chronic respiratory pathologies, or those on medications affecting lung function were excluded. Baseline and end-line demographic, physiological variables, and PFT parameters (forced vital capacity [FVC], forced expiratory volume in the first second [FEV1], FEV1/FVC, peak expiratory flow rate [PEFR]) were analysed using SPSS v.24 for inter-group comparisons (unpaired t-tests); intra-group (pre-post) comparisons (paired t-tests) with p≤0.05 considered significant.Result: Among 73 participants (Group A=36, Group B=37), at baseline, Group A had a higher FEV1/FVC ratio (0.77±0.02 vs. 0.76±0.03; unpaired t-test, p=0.01). Post-Pranayama, Group A showed significant improvements in pulse rate, FVC, FEV1, and FEV1/FVC (paired t-test, all p≤0.05). For all participants combined, significant post-intervention improvements were seen in weight, body mass index (BMI), systolic blood pressure (SBP), pulse rate (PR), respiratory rate (RR), and all PFT parameters (paired t-test, all p≤0.05) except for diastolic blood pressure (DBP).Conclusion: This study demonstrates that Pranayama practice significantly improves lung function and physiological parameters in both dietary groups. A minor baseline difference suggests that dietary patterns may influence respiratory health.